Combination of Sardine and Shark Oil High Content of Omega-3 and Squalene - Muhamad Musbah; Sugeng Heri Suseno; Uju Uju (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Sardine oil contain high concentration of  EPA but low of  DHA while shark is reverse. Shark oil  high contain of DHA and squalene but low EPA. This research aim to fortify the quality of  fish oil withomega-3 and squalen and improve the quality of fish oil. The combination of fish oil (sardine:shark) 1: 1, 1: 2, 1: 3, 1: 4, 2: 1, 3: 1 and 4:1 showed significant results on peroxide, anisidine, and total oxidation value, however free fatty acids analysis did not show the influence to the content value.  The best oxidation parameters value werefound (sardine: shark) (1:4) with peroxide was 5.44±0.06 mEq/kg, anisidine was 8.3±0.72 mEq/kg and total oxidation was 19.27±0.7mEq/kg. Fatty acids profile between  sardines and shark oil containedvarious SFA, MUFA and PUFA. Sardine oil which was added more to combination ratio will increase omega-3. Sample 1:4 had 43.16% squalene.